Current status and future challenges in transitioning to continuous bioprocessing of virus‐like particles. Issue 9 (30th June 2021) - Mittal, Manya; Banerjee, Manidipa; Lua, Linda HL; Rathore, Anurag S
Abstract: Virus‐like particles (VLPs) are bioengineered protein complexes that can serve as prophylactic vaccines due to favorable immunological characteristics like size, repetitive surface geometry and ability to induce both innate and adaptive immune responses, without being infectious. Large‐scale manufacturing of VLPs presents some interesting and unique challenges associated with removal of refractory contaminants to attain high product purity, improvement in structural homogeneity and colloidal stability. Recent advancements in production and purification of VLP‐based vaccines, such as application of monolithic multicolumn chromatography and inline concentration and diafiltration, have set a stage for implementation of continuous bioprocessing for commercial manufacturing of VLPs. The benefits of continuous bioprocessing have been well demonstrated for biotherapeutics, particularly monoclonal antibodies and small peptides. With the growing demand for affordable vaccines, the biopharmaceutical industry has shown increasing interest in establishing end‐to‐end continuous platforms. This article reviews major developments that have occurred in continuous processing for the manufacturing of VLPs. The major problems inherent in transitions from batch to continuous processing are also discussed, along with potential strategies to overcome the challenges. © 2021 Society of Chemical Industry (SCI).